Esqueleto y piel en la percepción de Bogotá (2008)
This case report depicts some of the results accomplished during the first stage of the research project Bogotá textual. Hopefully, the information gathered will allow for understanding the way Bogotá has changed over the last twenty years from a normative and juridical point of view. It focuses on the development plans undertaken by seven major´s offices from 1988 to 2004, and on the documents of some of the governmental bureaus in charge of the main programs, projects and budgets of each of those city administrations. This documental analysis pretends, in the first place, to identify, describe and explain discursive and textual mutations, as well as phraseological and denominational changes of social groups, urban situations and social problems; and secondly, it proposes a characterization of the different majors and the valorative orientation they gave to their term. Also, it is meant to identify and describe the continuities and ruptures undergone at this level.